A DANGEROUS COMBINATION OF TOBACCO SMOKING AND PULMONARY TUBERCULOSIS - Amrit Kumar Goel (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Smokers are more likely to get TB infection because smoking weakens the immune system and harms the lungs. It has been demonstrated that the onset of TB is associated with altered immunological response and numerous immune cell abnormalities, including those in macrophages, monocytes, and CD4 lymphocytes. The WHO proposed a larger emphasis on preventing TB exposures in 2010. Smoking has been linked to an increased chance of developing tuberculosis (TB) in multiple studies, along with coronary heart disease and cancer. By 2020, it is anticipated that TB and tobacco-related deaths, both of which are significant causes of mortality and morbidity, will total 8.4 million.Aim: A Dangerous Combination of Tobacco Smoking and Pulmonary TuberculosisMaterial and Method: The department of respiratory medicine was where the study was carried out. All individuals 10 years of age and older underwent a chest x-ray and symptoms examination to check for pulmonary tuberculosis. Sputum smear and culture examinations were used to assess those with chest symptoms and/or positive radiographs. About 5400 people were surveyed, and they served as the study's cases and controls. During the survey period, the illness status of the cases and controls was established, and at the time of the study in 1998, exposure to tobacco smoking was identified for both patients and controls.Results: 34 of 50 cases (68%) and 38 of 50 controls (76%) were present, giving a total of 72 of the 100 individuals (72%) available for interview; subsequent analysis was confined only to these individuals because exposure data were collected only from them. Since all the study population came from the rural villages which were homogenous with respect to social and demographic characteristics, it is reasonable to assume that the remaining subjects did not differ sociodemographically from the population interviewed.Conclusion: It's probable that smoking tobacco increases the risk of getting pulmonary tuberculosis. To quantify the incidence rate ratios between smokers and non-smokers and to increase the evidence for a causal link between tobacco use and pulmonary tuberculosis, additional studies employing various study designs and a follow-up time are required.Keywords: Sociodemographically, Tobacco, Smoking and Pulmonary Tuberculosis